2009
DOI: 10.1016/j.ejcts.2009.03.063
|View full text |Cite
|
Sign up to set email alerts
|

The role of CD133 in the identification and characterisation of tumour-initiating cells in non-small-cell lung cancer☆☆☆

Abstract: We have isolated and characterised a population of CD133-positive cells from NSCLC that is able to give rise to spheres and can act as tumour-initiating cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
162
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 193 publications
(174 citation statements)
references
References 17 publications
5
162
0
3
Order By: Relevance
“…CD44 + /CD24 + and CD44 + /CD24 -/low subpopulations derived from cell line A549 were characterized using their colony-and sphere-formation potential. CD133 is the most commonly reported cell surface marker that has been used to isolate CSCs from lung cancer cell lines and fresh tumor samples, but there is no consensus on the level of CD133 expression in cell line A549 [7,12,[32][33][34][35][36]. Our data demonstrate that 0.94% of A549 cells expressed the CD133 marker.…”
Section: Discussionmentioning
confidence: 68%
“…CD44 + /CD24 + and CD44 + /CD24 -/low subpopulations derived from cell line A549 were characterized using their colony-and sphere-formation potential. CD133 is the most commonly reported cell surface marker that has been used to isolate CSCs from lung cancer cell lines and fresh tumor samples, but there is no consensus on the level of CD133 expression in cell line A549 [7,12,[32][33][34][35][36]. Our data demonstrate that 0.94% of A549 cells expressed the CD133 marker.…”
Section: Discussionmentioning
confidence: 68%
“…+ cells and A549 cells may be due to unique characteristic of CD133 + cells [22][23][24]. It need to be noticed that Meng et al studied the CD133 + and CD133 -A549 cells and found that they exhibited similar abilities of colony formation, invasion [16].…”
Section: Discussionmentioning
confidence: 99%
“…The high expression of CD133 in ccRCC with favorable clinicopathological characteristics was an unexpected result, as CD133 has been applied as a putative CSC marker in numerous malignant tumors, and its high expression has been considered a poor prognostic factor. CD133 is currently applied as a cell-surface marker to isolate CSCs in malignant tumors of the colon, brain, lung, prostate, pancreas, liver, stomach and uterus (11,(25)(26)(27). A CD133…”
Section: Discussionmentioning
confidence: 99%